The Role of Breastfeeding on Respiratory Outcomes Later in Childhood - Di Filippo, Paola; Lizzi, Mauro; Raso, Massimiliano; Di Pillo, Sabrina; Chiarelli, Francesco; Attanasi, Marina (Frontiers in Pediatrics, 2022)
Background: Breastfeeding is associated with a lower risk of wheezing in early childhood, but its effect later in childhood remains unclear. We examined the associations of breastfeeding and respiratory outcomes in children aged 11 years. Materials and Methods: We performed an observational longitudinal study including 110 prepubertal children. Information about breastfeeding duration, wheezing and asthma was collected by questionnaires. At 11 years of age, we measured spirometry parameters, lung volumes, diffusing lung capacity and fractional exhaled nitric oxide. We used logistic and linear regression models to examine the associations of breastfeeding duration with the odds of asthma and lung function measures. All multivariable analyses were adjusted for sex, smoking during pregnancy, gestational age at birth, twins and mode of delivery (confounder model). Results: we found that breastfeeding duration was associated with FEV1 z-score (β=0.04, CI 95% (0.02-0.09)), FEF75 z-score (β=0.06, CI 95% (0.03-0.09)) and FEV1/FVC z-score (β=0.03, CI 95% (0.00-0.07)), but not with diffusing lung capacity and fractional exhaled nitric oxide. No association of breastfeeding duration with preschool wheezing, ever asthma and current asthma was documented. Conclusions: We showed that children breastfed for longer time presented higher FEV1, FEV1/FVC and FEF75 z-score values at 11 years of age compared to children breastfed for shorter time, suggesting a protective effect of breastfeeding on airways, and not on lung parenchyma (lung volumes and alveolar capillary membrane) or allergic airway inflammation. The positive effect of breastfeeding duration on lung function lays the foundation to promote breastfeeding more and more as effective preventive measure.